(untitled) (International Journal of Engineering and Computer Science, 2016)
With the availability of numerous different project development techniques it is highly complicated for software developers and project supervisors to assess the adequacy of agile processes as well as other traditional methods to the projects and modules. This paper briefly describes the advantages, limitations as well as comparison with other popular project development techniques to the agile methodology.